The Relationship Between Obesity, Overweight, and the Human Development Index in World Health Organization Eastern Mediterranean Region Countries - Amin Ataey; Elnaz Jafarvand; Davoud Adham; Eslam Moradi-Asl (Korean Society for Preventive Medicine, 2020)
Objectives Obesity is regarded as one of the most prominent health threats worldwide and a serious risk factor for non-communicable diseases, such as diabetes mellitus type 2, high blood pressure, cardiovascular diseases, and some types of cancer. Given the role that societal development-as reflected by the Human Development Index (HDI)-may play in the prevalence of obesity and overweight, this study aimed to investigate the degree to which the prevalence of obesity and overweight is affected by HDI and its components. Methods In this ecological study, the required data on HDI and its components were gathered from the latest report of the United Nations Development Program, and data on obesity and overweight were acquired from the latest reports published on the World Health Organization website. Statistical analyses were conducted using SPSS version 24.0. Results The prevalence of obesity was determined to be significantly higher among females than males, and the gross national index per capita was found to be significantly higher for males than females (p<0.05). Significant positive correlations were found between HDI and its components and sex, as well as indices of obesity and overweight. Conclusions A significant positive correlation exists between HDI and obesity. As policy-makers attempt to improve the general welfare of the people, they should be aware of potential unwanted effects of development on the risk of obesity and overweight among the population.